Barriers and facilitators to the implementation of the Assessment of Burden of Chronic Conditions tool in Dutch primary care: a context analysis - Onno C P Van Schayck; Danny Claessens; Esther A Boudewijns; Liset van Dijk; Marcia Vervloet; Lotte C E M Keijsers; Annerika H M Gidding-Slok (BMJ Open)
Objectives The Assessment of Burden of Chronic Conditions (ABCC) tool is developed to facilitate a personalised approach to care through assessment and visualisation of a patient’s experienced burden of disease, and integrating this in the conversation based on shared decision-making and individualised care plans. An indispensable step in the implementation process is an understanding of the context. The aim of this study is to perform a context analysis to identify barriers and facilitators to the implementation of the ABCC tool by healthcare providers (HCPs) in Dutch primary care.Design A qualitative context analysis was performed among HCPs prior to using the ABCC tool. The Consolidated Framework for Implementation Research was used to map contextual influences through semistructured interviews. A deductive coding process and content analysis was applied to identify barriers and facilitators for the implementation of the ABCC tool.Participants HCPs who participated as interventionists in an effectiveness study were recruited for this study.Results 17 HCPs (16 practice nurses and 1 general practitioner) participated. Data saturation was reached at the 11th interview. HCPs expected several major barriers to the implementation of the ABCC tool:too many different digital environments, high complexity in access, lack of time, no integration of the ABCC tool in guidelines and care standards, and patients not willing to adopt an active role in their care process. The major facilitators for implementation were a clear perception of the ABCC tool’s benefits, high compatibility with and relative advantage over current practices and being part of a progressive work culture that stimulates innovation.Conclusions This study provides insight in the barriers and facilitators to the implementation of an intervention in the patient–HCP conversation. Barriers were present in complexity, available resources, patient needs and resources, and external policies and incentives while facilitators were present in knowledge and beliefs, implementation climate and culture. These barriers and facilitators provide opportunities for the selection and tailoring of implementation strategies for the ABCC tool.